Evaluation of force exerted by tetrapods displaced by tsunami on caisson breakwater return wall. Issue 2 (2nd April 2020) - Hamano, Go; Ishii, Hidenori; Iimura, Kotaro; Takabatake, Tomoyuki; Stolle, Jacob; Esteban, Miguel; Shibayama, Tomoya
ABSTRACT: Tsunamis can cause large damage to breakwaters and other protection structures placed along the coastline. The strong flows generated by such waves can move the armor units of composite breakwaters, leading to large impact forces on the caissons behind them. In the present work laboratory experiments were carried out in a flume to determine the forces that can result from such impacts. Then, an empirical equation that would allow the estimation of these forces was proposed, with the aim of facilitating the construction of returning walls and parapets situated on top of caissons.